Evidence of blood-brain barrier dysfunction in human cerebral malaria. - Brown, H; Hien, T; Day, N; Mai, N; Chuong, L; Chau, T; Loc, P; Phu, N; Bethell, D; Farrar, J; Gatter, K; White, N; et al. (1999)
Patients infected with the malaria parasite Plasmodium falciparum may develop a diffuse reversible encephalopathy, termed cerebral malaria. It is unclear how the intraerythrocytic parasite, which sequesters in the cerebral microvasculature but does not enter the brain parenchyma, induces this neurological syndrome. Adhesion of parasitized red blood cells in the brain microvasculature is mediated by specific receptors on the host endothelium, including intercellular adhesion molecule (ICAM)-1, CD36 and CD31. Leucocyte binding to cerebral endothelial cells in culture induces intracellular signalling via ICAM-1. The hypothesis that parasitized red blood cells binding to receptors on cerebral endothelial cells causes changes in the integrity of the blood-brain barrier was tested. Immunohistochemistry was used to examine the blood-brain barrier in human cerebral malaria, with antibodies to macrophage and endothelial activation markers, intercellular junction proteins, and plasma proteins. The distribution of the cell junction proteins occludin, vinculin and ZO-1 were altered in cerebral malaria cases compared to controls. While fibrinogen was the only plasma protein detected in the perivascular space, there was widespread perivascular macrophage activation, suggesting that these cells had been exposed to plasma proteins. It was concluded that functional changes to the blood-brain barrier occur in cerebral malaria, possibly as a result of the binding of parasitized red blood cells to cerebral endothelial cells. These changes require further examination in vitro.